Examination of Generalized Statistical Convergence of Order α on Time Scales. (23rd August 2022) - Çinar, Muhammed; Işik, Mahmut
Abstract : In this paper, we introduce the concepts of deferred statistical convergence of order α and strongly deferred Cesàro summable functions (real valued) of order α on time scales and give some relationships between deferred statistical convergence of order α and strongly deferred Cesàro summable functions (real valued) of order α on time scales.